2022
DOI: 10.1371/journal.pone.0271623
|View full text |Cite
|
Sign up to set email alerts
|

Development, characterization and In-vitro evaluation of guar gum based new polymeric matrices for controlled delivery using metformin HCl as model drug

Abstract: Currently, hydrogels are considered as ideal biomaterials due to their unique structure and characteristics that facilitates considerable hydrophilicity, swelling, drug loading and release. In this study, we report pH-responsive GG-MAA-AMPS hydrogel delivery system prepared via free radical polymerization technique. Hydrogels were loaded with Metformin HCl as a model drug. Hydrogels were characterized through Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), differential scannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…The glass transition’s temperature was estimated to be close to 290 °C. AMPS indicated a sharp endothermic peak around 202 °C, which is attributed to the decomposition of sulphonic acid groups [ 69 ]. DSC data of the rutin sample showed an endothermic phase between 56 °C and 150.78 °C resulting from water loss.…”
Section: Resultsmentioning
confidence: 99%
“…The glass transition’s temperature was estimated to be close to 290 °C. AMPS indicated a sharp endothermic peak around 202 °C, which is attributed to the decomposition of sulphonic acid groups [ 69 ]. DSC data of the rutin sample showed an endothermic phase between 56 °C and 150.78 °C resulting from water loss.…”
Section: Resultsmentioning
confidence: 99%
“…The DSC analysis results are shown in Figure 3 . AMPS showed a sharp endothermic peak at 202 °C, indicating the decomposition of the sulphonic acid groups [ 34 ]. HP-βCD showed water loss at 77.70 °C and a melting peak around 344.12 °C.…”
Section: Resultsmentioning
confidence: 99%
“…The pH dependent release can be brought on by the different levels of hydrogen bonding interaction and electrostatic attraction between the two species at various pH values. As the pH level was raised, there was a concurrent increase in both swelling and osmotic pressure within the polymeric network, leading to an enhanced release of drugs at higher pH solution [40] . Singh et al.…”
Section: Resultsmentioning
confidence: 99%
“…As the pH level was raised, there was a concurrent increase in both swelling and osmotic pressure within the polymeric network, leading to an enhanced release of drugs at higher pH solution. [40] Singh et al also observed the fast release of the drug in high pH solution than neutral and low pH solutions. [41] The MFH enters the polymer network and spreads through the aqueous channel to the surface of the CMLB-co-poly(SA)-cl-poly(MBA) hydrogel and thus sustained release occurs.…”
Section: Drug Loading and Release Studymentioning
confidence: 94%
See 1 more Smart Citation